A DLC/diamond bilayer approach for reducing the initial friction towards a highbearing capacity - Amaral, M. (2012)
Sliding contact mechanics is used to account for the net increase of the bearing capacity of high wear-resistant CVD diamond coatings when an outer layer of a DLC lubricant film is deposited on their top surface. Experimental results,namely the critical failure load, taken from reciprocating ball-on-plate tribological testing of such DLC/diamond bilayers, are on the basis of this statement. DC magnetron sputtering was used to grow thin DLC lubricant coatings (non-hydrogenated and hydrogenated varieties) on the top of CVD diamond films (microcrystalline and nanocrystalline types). The application of the von Mises maximum yield parameter (J2)1/2 criterion demonstrates to be an adequate method for designing low-friction and high-bearing capacity systems for high-demanding tribological applications. Calculation of (J2)1/2 supports that the most significant increase observed on the coatings’ bearing capacity (from 20 N to 60 N) takes place when microcrystalline diamond is coated by hydrogenated DLC that decreases the initial friction coefficient peak (from 0.76 to 0.41).